Current suburbanisation trends in the Czech Republic and spatial transformation of retail - Ptáček Pavel; Szczyrba Zdeněk (Journal for Geography, 2007)
The main topic of the article is commercial suburbanisation in the Czech Republic on the example of changes in retail. In the first part it is described the mechanism of suburbanisation, its causes, forms and social, economic and ecological consequences. In the next part we deal with the transition of retail, its spatial dimension with special regard to suburbanisation process. Spatial changes in retail on the example of Olomouc and their causes and consequences are described.